2022
DOI: 10.3390/medicines9050031
|View full text |Cite
|
Sign up to set email alerts
|

Unforeseen Outcomes Post Treatment for Radiation Induced Trismus: A Case Report

Abstract: Post radiotherapy radiation trismus presents significant concerns for a patient’s quality of life and for the clinical monitoring for recurrence of head and neck oncology. Current treatments include scar band release surgery that has been shown to be safe and effective. We present a case with a rare, post-operative complication of difficulty of mouth closure that can pose a significant impact on quality of life that should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Radiation-induced trismus (RIT), one of the most dreadful side effects of C-CRT, is difficult to predict with a high degree of accuracy and has a terrible impact on the quality of life of those who experience it. [4][5][6] RIT may result in many adverse health consequences, including dysphagia, dysgeusia, ageusia, dental disease, orofacial pain, oral infections, and even osteoradionecrosis and difficulties with intubation. 7,8 Although much remains unknown about the process, it is commonly accepted that radiation-induced inflammation, endothelial damage, hypoxia, and fibrosis are the primary reasons for its onset and development.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation-induced trismus (RIT), one of the most dreadful side effects of C-CRT, is difficult to predict with a high degree of accuracy and has a terrible impact on the quality of life of those who experience it. [4][5][6] RIT may result in many adverse health consequences, including dysphagia, dysgeusia, ageusia, dental disease, orofacial pain, oral infections, and even osteoradionecrosis and difficulties with intubation. 7,8 Although much remains unknown about the process, it is commonly accepted that radiation-induced inflammation, endothelial damage, hypoxia, and fibrosis are the primary reasons for its onset and development.…”
Section: Introductionmentioning
confidence: 99%
“…When coronoidectomy alone is insufficient to achieve adequate oral motoric function or when trismus recurs, further surgical management may be necessary. Sivam et al 7 reported a tonsillar SCC survivor with worsening trismus and pain despite bilateral coronoidectomy and botulinum toxin injections. They successfully increased her MMO from 2 to 40 mm by performing 34 sessions of hyperbaric oxygen therapy followed by surgical intraoral scar band release, bilateral temporalis muscle flap, complete bilateral posterior molar extraction, mandible corticotomy, and tracheostomy 7 .…”
mentioning
confidence: 99%
“…Sivam et al 7 reported a tonsillar SCC survivor with worsening trismus and pain despite bilateral coronoidectomy and botulinum toxin injections. They successfully increased her MMO from 2 to 40 mm by performing 34 sessions of hyperbaric oxygen therapy followed by surgical intraoral scar band release, bilateral temporalis muscle flap, complete bilateral posterior molar extraction, mandible corticotomy, and tracheostomy 7 . Finally, surgical treatment is considered complete when the patient has significantly regained their oral function and is satisfied with the results.…”
mentioning
confidence: 99%